Cocoa intoxication in domestic and street dogs: A comparative study - Alahmed, Jala Amir Salman; Al-Rufaei, Iqbal A.; Alwan, Nawras A. (Archives of Veterinary Science, 2024)
Chocolate intoxication can be life-threatening to dogs and cats with high morbidity and mortality. The current study aims to compare the toxic effect of dark chocolate on domestic dogs versus street dogs. Eighteen male dogs were used in this study, nine of each of domestic dogs and street dogs. The experiment continued for seven consecutive days. After three days, blood samples were collected as a control, and one dog from each group was sacrificed for negative control histopathological purposes. The same animals of both groups received a mixture of the standard diets and cocoa powder (1g / Kg BW / day) for four days. Clinical signs appeared faster in domestic dogs than in street dogs. Liver enzymes and oxidative stress indicators were elevated after four days in both street dogs the domestic dogs but not in their control groups. Furthermore, there was a significant increase in lipid profile except for HDL in the groups treated with cocoa compared to the control groups. The same results were noticed regarding total protein, urea, and creatinine since they significantly increased against their controls. In conclusion, cocoa is toxic to both domestic and street dogs in the same way except for the starting of the clinical signs where the domestic dogs were affected earlier than street dogs.